Old Communities, New Controversies: the Community of Macedonian Speaking Muslims between Ethnicity and Religion - Damjanovski, Ivan (My University, 2021)
By focusing on the contemporary developments in North Macedonia whilst having in mind the religious bases of the process of creation of national identities in the Balkans, the article addresses the correlation between ethnic identity, religion and politicization as a case of intertwinement and imbrications between these phenomena. In a broader perspective, reflecting the academic debate on the nature of ethnic identities, the article criticizes the essentialist conceptions of the fixed, durable and objective properties of ethnic identification and perceives identities as fluid constructs that are often susceptible to transformations. The article focuses on the peculiar case of the Macedonian speaking Muslim community where religion emerges as a potent source for ethnic identification. Accordingly, the article investigates how overlaps between the ethno-national and religious identities become a principal determinant of three perspectives: the ambivalent treatment and perception of inclusion and discrimination from the ethnic Macedonians, assimilation with other Muslim ethnicities and the process of formation of a distinct ethnic group.
Keywords: Macedonian speaking Muslims, ethnic identity, religion, politicisation, language